The concise PRINCE2® : principles and essential themes - Bentley, Colin (IT Governance Publishing Ltd, 2019)
This guide explains the fundamental principles of PRINCE2 2017, enabling you to review essential themes before taking your PRINCE2 Foundation exam. Following accreditation, it serves as a reference guide to help you manage ongoing PRINCE2 projects within your organisation.
Keywords: Project management -- Handbooks, manuals, etc.; Electronic data processing.; Production management.; elektronické knihy; electronic books